Genetic Issues in the Diagnosis of Dystonias - Petrucci, Simona; Valente, Enza Maria (Frontiers in Neurology, 2013)
Dystonias are heterogeneous hyperkinetic movement disorders characterized by involuntary muscle contractions which result in twisting and repetitive movements and abnormal postures. Several causative genes have been identified, but their genetic bases still remain elusive. Primary Torsion Dystonias (PTDs), in which dystonia is the only clinical sign, can be inherited in a monogenic fashion, and many genes and loci have been identified for autosomal dominant (DYT1/TOR1A; DYT6/THAP1; DYT4/TUBB4a; DYT7; DYT13; DYT21; DYT23/CIZ1; DYT24/ ANO3; DYT25/GNAL) and recessive (DYT2; DYT17) forms. However most sporadic cases, especially those with late onset, are likely multifactorial, with genetic and environmental factors interplaying to reach a threshold of disease. At present, genetic counseling of dystonia patients remains a difficult task. Recently non-motor clinical findings in dystonias, new highlights in the pathophysiology of the disease and the availability of high-throughput genome-wide techniques are proving useful tools to better understand the complexity of PTD genetics. We briefly review the genetic basis of the most common forms of hereditary PTDs, and discuss relevant issues related to molecular diagnosis and genetic counseling.